Pelatihan Kreativitas Guru Tafsir Amaly Di Pondok Pesantren Al-Urwatul Wutsqo Jombang - Ali Mustofa; Moch. Sya'roni Hasan; Nurul Indana (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2023)
The purpose of this service is to describe the Creativity Training of Amaly Tafsir Teachers at the Al-Urwatul Wutsqo Islamic Boarding School, Jombang. The implementation method is carried out as an approach to community service at the Al-Urwatul Wutsqo Islamic Boarding School, Jombang. consists of 5 stages, namely: 1. The first stage, approaching the board of teachers and caregivers 2. The second stage, conducting preliminary data collection. 3. The third stage, identify the problem. 4. The fourth stage, analyze each problem. 5. The final stage is determining a temporary solution. The result of this dedication is that the creativity of the teacher's Interpretation of Amaly can be done by means of the teacher having to do a number of things, including: The teacher teaches in the classroom not only to focus on the lecture method, but to use the discussion method, ask questions. answer and others, teachers sometimes accompany the lesson by motivating their students. Interspersing the Tafsir Amaly lesson with the Qur'an Hadith lesson, the teacher forms students into several groups to make games from verses of the Qur'an. The teacher asks the children to make yells or tell humorous stories and sometimes the teacher asks the children to sing simultaneously.